2008
DOI: 10.1038/ja.2008.43
|View full text |Cite
|
Sign up to set email alerts
|

SAR Study of a Novel Triene-ansamycin Group Compound, Quinotrierixin, and Related Compounds, as Inhibitors of ER Stress-induced XBP1 Activation

Abstract: In the course of screening for an inhibitor of ER stress-induced XBP1 activation, we isolated a new member of the triene-ansamycin group compound, quinotrierixin, from a culture broth of Streptomyces sp. PAE37. Quinotrierixin inhibited thapsigargin-induced XBP1 activation in HeLa cells with an IC 50 of 0.067 mM. We found that other triene-ansamycin group compounds such as demethyltrienomycin A and mycotrienin I also inhibited ER stress-induced XBP1 activation. Moreover, we performed SAR study of twelve triene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…24, 30 In the course of further screening for an inhibitor of ER stress-induced XBP1 activation, we isolated toyocamycin 25 from a culture broth of an Actinomycete strain (Figure 1a). As shown in Figure 1b, 0.1 μℳ thapsigargin, an inhibitor of the ER calcium pump (SERCA), elevated XBP1-luciferase activity about 2.5-fold more than the control in HeLa/XBP1-luc cells.…”
Section: Resultsmentioning
confidence: 99%
“…24, 30 In the course of further screening for an inhibitor of ER stress-induced XBP1 activation, we isolated toyocamycin 25 from a culture broth of an Actinomycete strain (Figure 1a). As shown in Figure 1b, 0.1 μℳ thapsigargin, an inhibitor of the ER calcium pump (SERCA), elevated XBP1-luciferase activity about 2.5-fold more than the control in HeLa/XBP1-luc cells.…”
Section: Resultsmentioning
confidence: 99%
“…We have also reported that novel trieneansamycin group compounds, quinotrierixin and trierixin, inhibited ER stress-induced XBP1 mRNA splicing in HeLa cells. [15][16][17][18] In this study, we found that quinotrierixin inhibited protein synthesis. Moreover, we investigated the relationship between quinotrierixin-inhibited ER stress-induced XBP1 mRNA splicing and protein synthesis.…”
mentioning
confidence: 75%
“…Quinotrierixin, trierixin, and trienomycin A were prepared as described in our previous reports. 15,17) Cytotrienin A was kindly provided by Dr. H. Osada (RIKEN, Japan). Cycloheximide, anisomycin, and puromycin were purchased from Sigma (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…It was first identified by the Tashiro group in 2007, as a specific inhibitor of ER stress-induced XBP1 mRNA splicing (Kawamura et al, 2008a). QT dose-dependently inhibits TG-induced XBP1 splicing in Hela cells with an IC50 of 0.067 μM (Kawamura et al, 2008b). However, a later study from the same group demonstrated that QT inhibits the protein production of UPR genes, including the 78-kDa glucose-regulated protein (GRP78), C/EBP homologous protein (CHOP), ERdj4 and P58ipk (Yamamoto et al, 2011).…”
Section: Discussionmentioning
confidence: 99%